2018
DOI: 10.1002/art.40535
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐Like Receptor 9 Deficiency Breaks Tolerance to RNA‐Associated Antigens and Up‐Regulates Toll‐Like Receptor 7 Protein in Sle1 Mice

Abstract: ObjectiveToll‐like receptors (TLRs) 7 and 9 are important innate signaling molecules with opposing roles in the development and progression of systemic lupus erythematosus (SLE). While multiple studies support the notion of a dependency on TLR‐7 for disease development, genetic ablation of TLR‐9 results in severe disease with glomerulonephritis (GN) by a largely unknown mechanism. This study was undertaken to examine the suppressive role of TLR‐9 in the development of severe lupus in a mouse model.MethodsWe cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 54 publications
9
29
2
Order By: Relevance
“…To determine whether antibiotic (Abx) treatment alters the immunological phenotypes in B6 and TLR9-deficient mice, we examined splenic weight, immunological traits in spleen and immunoglobulin (Ig) production in serum. Previous data from the Fairhurst lab has shown that TLR9 -/mice develop mild splenomegaly compared to B6 mice [49]. However, in this study we did not observe an increase in splenic weight.…”
Section: Impact Of Tlr9 On Microbiotacontrasting
confidence: 94%
See 3 more Smart Citations
“…To determine whether antibiotic (Abx) treatment alters the immunological phenotypes in B6 and TLR9-deficient mice, we examined splenic weight, immunological traits in spleen and immunoglobulin (Ig) production in serum. Previous data from the Fairhurst lab has shown that TLR9 -/mice develop mild splenomegaly compared to B6 mice [49]. However, in this study we did not observe an increase in splenic weight.…”
Section: Impact Of Tlr9 On Microbiotacontrasting
confidence: 94%
“…However, the period of Abx administration was shortened by 2 months to avoid complications in the experiment from the mortality, observed at 6mos Sle1TLR9 -/mice. Consistent with our previous findings [49], Sle1TLR9 -/developed an increase in splenomegaly compared to Sle1 controls. However, Abx administration did not reduce splenomegaly, in contrast to the findings by Mu Q and colleague in MRL-lpr mice [112] ( Figure 3.2 A).…”
Section: Impact Of Gut Microbiota On Sle1 and Sle1tlr9 -/-supporting
confidence: 92%
See 2 more Smart Citations
“…However, TLR7 signaling was normal in SLE B cells (Gies et al, 2018). Moreover, when lupus-prone Sle1 mice were crossed with TLR9 −/− mice, SLE pathology was exacerbated, and TLR7 expression was increased, leading to increased antigen presentation on DCs (Celhar et al, 2018). Similar results were also observed in TLR9 −/− mice treated epicutaneously with imiquimod, which induces local inflammation, as compared to wild-type mice (Liu et al, 2018).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%